Antioxidative and Anti-Inflammatory Properties of Cannabidiol - Sinemyiz Atalay; Iwona Jarocka-Karpowicz; Elzbieta Skrzydlewska (MDPI AG, 2019)
Cannabidiol (CBD) is one of the main pharmacologically active phytocannabinoids of Cannabis sativa L. CBD is non-psychoactive but exerts a number of beneficial pharmacological effects, including anti-inflammatory and antioxidant properties. The chemistry and pharmacology of CBD, as well as various molecular targets, including cannabinoid receptors and other components of the endocannabinoid system with which it interacts, have been extensively studied. In addition, preclinical and clinical studies have contributed to our understanding of the therapeutic potential of CBD for many diseases, including diseases associated with oxidative stress. Here, we review the main biological effects of CBD, and its synthetic derivatives, focusing on the cellular, antioxidant, and anti-inflammatory properties of CBD.